Elevation, aspect, and slope influence woody vegetation structure and composition but not species richness in a human-influenced landscape in northwestern Yunnan, China - Cheng, Zhongqian; Aakala, Tuomas; Larjavaara, Markku (Frontiers in Forests and Global Change, 2023)
Elevation-for-latitude substitution offers a tool for studying the influence of temperature and precipitation variability on vegetation structure and composition. Understanding how elevation, aspect, and slope influence vegetation patterns may help in predicting how climate change influences human forest usage and in developing strategies for ensuring the sustained provision of ecosystem services. However, most ecological studies have been carried out in protected areas, leaving forest areas used by humans to lesser attention. Therefore, we asked how elevation, aspect, and slope impact the vegetation on a human-influenced mountain. We measured woody vegetation size, richness, and composition on a mountain with plots set systematically in four cardinal directions at 100-m elevational intervals from the peak, from 1900 m to 4200 m above sea level, in the Hengduan Mountains in eastern Himalaya, southwestern China. We quantified how tree maximum height, basal area, aboveground biomass (AGB), tree and shrub species richness, and woody species composition changed with elevation, aspect, and slope. Based on generalized linear models, the maximum tree height, tree basal area, and woody species AGB followed a unimodal trend along elevational gradients, with tree height and basal area peaking at 3100 m, while AGB was highest at 3300 m and somewhat higher on the southern slope. Basal area increased with slope degree. Neither tree nor shrub species richness was influenced by elevation, aspect, or slope. According to canonical correspondence analysis and TWINSPAN classification, elevation and north-south orientation of the slope were major factors influencing woody species compositions, and vegetation was classified into five types of communities. Our results indicated that the influences of elevation, aspect, and slope on woody vegetation structure were similar in a human-influenced forested mountain area as in protected mountain landscapes based on the literature. However, as forests in this area are used more intensively at low and middle elevations of the southern and western slopes, where aridity restricts tree size and AGB, climate change is likely to challenge traditional harvesting practices and place pressure on moving forest usage to higher altitudes.